Complicaciones gastrointestinales y su efecto en el estado nutricional de pacientes con Parálisis Cerebral infantil. - Orellana Ramon, Marlin Juleysi; Quezada Lomas, Ambar Kristel (My University, 2024)
Introduction: Cerebral palsy as of 2007 is considered a neurological disability associated with mainly motor functional restrictions, generating postural, mobility and coordination limitations, affecting 1.5-3 per 1,000 live newborns. Objective: Describe the effect of gastrointestinal complications on the nutritional status of patients with Infantile Cerebral Palsy between 2 and 20 years old. Methods: The selection of the articles was based on the PRISMA Method in which 3,148 articles were obtained and, based on the exclusion criteria, the quality of 107 studies was analyzed to finally select 30 articles. For the collection, tabulation, extraction and synthesis of information, an analytical matrix was created in the Microsoft Excel manager. Conclusions: Gastrointestinal complications are highly prevalent in pediatric patients with infantile cerebral palsy, representing a significant risk condition for the development of malnutrition and specific nutritional deficiencies, given that they negatively affect the intake, digestion and absorption of nutrients, decreasing anthropometric indicators. biochemical and dietary aspects of nutritional status. Therefore, greater severity of gastrointestinal complications correlates with greater nutritional compromise. Despite this, more longitudinal studies and clinical trials are required that cover these conditions in the population with cerebral palsy. Keywords: Cerebral Palsy; gastrointestinal diseases; Nutritional condition; Malnutrition.
Introducción: La parálisis cerebral a partir del 2007 es considerada una discapacidad neurológica asociada a restricciones funcionales principalmente motoras, generando limitaciones posturales, de movilidad y coordinación, afectando a 1.5-3 por cada 1.000 recién nacidos vivos. Objetivo: Describir el efecto de las complicaciones gastrointestinales en el estado nutricional de pacientes con Parálisis Cerebral Infantil entre 2 y 20 años. Métodos: La selección de los artículos se basó en el Método PRISMA en el que se obtuvieron 3,148 artículos y, a partir de los criterios de exclusión, se analizó la calidad de 107 estudios para finalmente seleccionarse 30 artículos. Para la recolección, tabulación, extracción y síntesis de información, se realizó una matriz analítica en el gestor Microsoft Excel. Conclusiones: Las complicaciones gastrointestinales son altamente prevalentes en pacientes pediátricos con parálisis cerebral infantil, representando una condición de riesgo significativa para el desarrollo de desnutrición y deficiencias nutricionales específicas, dado que afectan negativamente la ingesta, digestión y absorción de nutrientes, disminuyendo los indicadores antropométricos, bioquímicos y dietéticos del estado nutricional. Por lo tanto, una mayor gravedad de las complicaciones gastrointestinales se correlaciona con un mayor compromiso nutricional. A pesar de ello se requieren más estudios longitudinales y ensayos clínicos que abarquen estas condiciones en la población con parálisis cerebral. Palabras clave: Parálisis Cerebral; Enfermedades gastrointestinales; Estado nutricional; Desnutrición.
Keywords: PARÁLISIS CEREBRAL; ENFERMEDADES GASTROINTESTINALES; ESTADO NUTRICIONAL; DESNUTRICIÓN